The Effect of Long-Term Exercise on the Production of Osteoclastogenic and Antiosteoclastogenic Cytokines by Peripheral Blood Mononuclear Cells and on Serum Markers of Bone Metabolism - J. Kelly Smith; Rhesa Dykes; David S. Chi (Journal of Osteoporosis)
Although it is recognized that the mechanical stresses associated with physical activity augment bone mineral density and improve bone quality, our understanding of how exercise modulates bone homeostasis at the molecular level is lacking. In a before and after trial involving 43 healthy adults, we measured the effect of six months of supervised exercise training on the spontaneous and phytohemagglutinin-induced production of osteoclastogenic cytokines (interleukin-1α, tumor necrosis factor-α), antiosteoclastogenic cytokines (transforming growth factor-β1 and interleukins 4 and 10), pleiotropic cytokines with variable effects on osteoclastogenesis (interferon-γ, interleukin-6), and T cell growth and differentiation factors (interleukins 2 and 12) by peripheral blood mononuclear cells. We also measured lymphocyte phenotypes and serum markers of bone formation (osteocalcin), bone resorption (C-terminal telopeptides of Type I collagen), and bone homeostasis (25 (OH) vitamin D, estradiol, testosterone, parathyroid hormone, and insulin-like growth factor 1). A combination of aerobic, resistance, and flexibility exercises done on average of 2.5 hours a week attenuated the production of osteoclastogenic cytokines and enhanced the production of antiosteoclastogenic cytokines. These changes were accompanied by a 16% reduction in collagen degradation products and a 9.8% increase in osteocalcin levels. We conclude that long-term moderate intensity exercise exerts a favorable effect on bone resorption by changing the balance between blood mononuclear cells producing osteoclastogenic cytokines and those producing antiosteoclastogenic cytokines. This trial is registered with Clinical Trials.gov Identifier: NCT02765945.